The Impact of Good Corporate Governance Mechanisms on Bank Performance Through the Implementation of Green Banking - Susilawati, Susi; Rini, Nova; Hasanah, Nur (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Good corporate governance emphasizes the importance of effective supervision by the board of directors and audit committee in overseeing bank policies and practices, including environmental policies. A strong supervisory structure, which is a part of GCG, can assist banks in identifying, measuring, and managing environmental risks more effectively. Through proper risk management, banks can mitigate the likelihood of adverse impacts on the bank's financial performance. This study aims to analyze the effectiveness of supervision for the internal company policymakers on bank financial performance given the requirement for green banking disclosure. The research design is causality using organizations, i.e., banks listed on the IDX-IC Share (Indonesian Stock Exchange) for the 2019 – 2022 period as the unit of analysis. The number of samples consisted of 103 companies annual data, while the data analysis used unbalanced panel data regression. The research results show that good corporate governance mechanisms (gender diversity, board size) and green banking affect bank performance, while audit committee size does not affect bank performance. Gender diversity does not affect green banking, while board size and audit committee size affect green banking. Green banking is only able to moderate the influence of board size on the bank’s performance.